The study of drying parameter of carrageenan using spray dryer - Adilah, Abd Rashid (2013)
This research is conducted to study the effect of inlet temperature of spray dryer,concentration of feed solution, and the feed flow rate of spray dryer on the moisture content,outlet temperature,yield,and the existent of carrageenan compound in the seaweeds powder produced by spray dryer.Prior the spray drying,the extraction process needs to be carried out.The extraction process involves five steps including pre-rinsing carrageenan containing seaweed, cooking the seaweed with an aqueous solution containing potassium hydroxide(KOH),washing the seaweed in neutralizing bath, rinsing the seaweed in water,and last but not least is drying and chopping the seaweed.Then,the extracted carrageenan solution is fed into the spray dryer to get the powder form product of carrageenan.Analysis on the outlet temperature of the spray dryer gives the increasing reading of outlet temperature when the inlet temperature and the feed concentration value were increased while decreasing with the increasing of the pump speed.For the analysis on moisture content,the increasing of inlet temperature and pump speed resulting the decreasing of the moisture content. The highest yield was obtained when the feed concentration was high and low at the low inlet temperature and pump setting.While the moisture content was increasing when the feed concentration was increases.The study showed that the carrageenan compounds exist in all the products and not very affected by those parameters changing by undergoing the FTIR analysis.This shows that spray drying method can protect the composition of polymer contained in the carrageenan from being denatured.